Association Between Prenatal Exposure to Organochlorine Pesticides and Telomere Length in Neonatal Cord Blood - Ying Jiang; Ziyuan Xu; Meng Wang; Hongxiu Liu; Yuanyuan Li; Shunqing Xu (Toxics)
Objectives: Environmental exposure may affect the telomere length (TL) of newborns, which is considered as an early biomarker indicating susceptibility for later life diseases. However, the effects of prenatal organochlorine pesticide (OCP) exposure on newborn TL remain unclear. This study aimed to investigate the association between prenatal exposure levels of OCPs during pregnancy and TL in neonatal cord blood. Methods: A total of 168 mother–infant pairs from a birth cohort in Wuhan, China, were included this study. The concentrations of hexachlorocyclohexanes (HCHs, including β-HCH, α-HCH, and γ-HCH), p,p’-dichlorodiphenyltrichloroethane (p,p’-DDT) and its metabolites (p,p’-dichlorodiphenyldichloroethane, p,p’-DDD; p,p’-dichlorodiphenyldichloroethylene, p,p’-DDE) were measured in cord blood. The associations between the OCPs and the TL in newborns were analyzed by a generalized linear regression model. Stratified analyses by newborn sex, maternal gestational weight gain, and pregnancy body mass index (BMI) were performed to evaluate if the associations were modified by these factors. Results: The detection rates of various OCPs ranged from 50.9% to 100.0%. The median concentration of p,p’-DDE was the highest (33.90 ng/g lipid), followed by β-HCH (8.67 ng/g lipid), and the median concentrations of the other OCPs were between 0.12 and 0.33 ng/g lipid. Among the all newborns, a two-fold increase in the γ-HCH concentration in the cord blood was significantly associated with a 0.024 (95% CI: −0.041, −0.007) decrease in the TL. After stratification by newborn sex, the inverse association between γ-HCH and the TL was only statistically significant in boys, but not in girls (P for interaction <0.05). In addition, after stratification by pre-pregnancy BMI, β-HCH and p,p’-DDT concentrations were significantly associated with a decreased TL in the overweight pre-pregnancy BMI group [−0.111 (95% CI: −0.203, −0.018) and −0.036 (95% CI: −0.049, −0.023), respectively]. Conclusions: Prenatal exposure to OCPs during pregnancy was associated with a decreased neonatal telomere length, which may be affected by the newborn sex and pre-pregnancy BMI. These findings may provide new insights into the mechanisms underlying OCP-induced adverse health effects.